Nerve agents – a clear and present danger to mankind - Stojiljković, Miloš P. (Scripta Medica, 2019)
This editorial is written on the occasion of the 25th anniversary of the infamous sarin and VX terrorist attacks in Japan, in order to increase the awareness of the potential terrorist use of nerve agents and to urge the preparedness to cope with its consequences. Nerve agents are extremely toxic organophosphorus acetylcholinesterase inhibitors, divided in three known groups: G-, V- and A-agents. G-agents tabun, sarin and soman were synthesised in Nazi Germany (1938-1944), V-agents including VX by the British in the 1950s and A-agents or Novichok agents between 1971 and 1993 in the Soviet Union. The use or alleged use of tabun and sarin was mentioned in connection with the Iraq-Iran war (1980-1988) and the Syrian conflict in 2013 and 2017. Sarin and VX were used for terrorist purposes by the Japanese religious sect AUM Shinrikyo in 1994 and 1995. An assassination of Kim Jong Nam with VX took place in Kuala Lumpur, Malesia in 2017, while the 2018 Salisbury and Amesbury poisonings in the UK were ascribed to the so-called Novichok agent A234. Milder cases of poisoning with nerve agents is accompanied by predominantly muscarinic symptomatology and more massive intoxications with mainly nicotinic and central symptoms. Treatment consists of use of atropine, oximes and anticonvulsants.